Avoiding plagiarism using Mendeley in Indonesian higher education setting - Andi Anto Patak; Muhammad Tahir (International Journal of Evaluation and Research in Education (IJERE), 2019)
People who plagiarize have a complex problem. Plagiarism could be by accident, by mistake, or on purpose. This research aims at exploring the reasons for plagiarizing and the significance of citing and referencing using Mendeley to avoid plagiarism. Four Indonesian Mendeley Advisors were interviewed online using convenient sampling technique. This study revealed that reasons for plagiarizing are time restriction, laziness, and busy. The significance of citing and referencing using Mendeley to avoid plagiarism are (1) confirm, justify, and claim the issue conveyed in scientific work; (2) highlight a particular idea; (3) criticize or approve the premise of others, and (4) build argument. Mendeley usage acquaintance for scientific writing is expected to be practical tools for avoiding plagiarism and promote academic honesty in the setting of higher education. However, the role of supervisor is crucial to provide useful feedback for their students’ writing to help students avoid plagiarism. Besides, university should create comfortable academic environment by providing free seminar and workshop on academic writing to educate students avoid plagiarism.